ANALYSIS OF ABNORMAL RETURN AND TRADING VOLUME ACTIVITY BEFORE AND AFTER THE LQ45 COMPANY CASH DIVIDEND ANNOUNCEMENT FOR THE 2020 PERIOD - Dewi, Reza Kusuma; Budianto, Erwin; Dhevyanto, Benny (Transpublika Publisher, 2022)
An increase in the trading volume of dividend-declaring shares at a particular moment may indicate that the company is performing well and has promising prospects. The dividend announcement includes crucial information for investors seeking abnormal returns. This study seeks to determine and assess whether there is a difference between AR and TVA before to and following the release of cash dividends. This study's data analysis method is a parametric statistical data analysis method. This method is used to statistically evaluate population parameters, or in other words, to test population size using pre-selected sample data and a significance level () of 0.05 or 5%. A data set is considered regularly distributed if asym.sig is less than 0.05. Sig. 0.277 > 0.05 indicates that there is no change in the average abnormal return before and after the declaration of cash dividends for LQ45 Company 2020. The findings of evaluating the sample data for trading volume activity indicate, with a significance level of 0.000 < 0.05, that there is a difference in trading volume activity before and after the release of cash dividends for LQ45 Company 2020. A significant negative abnormal return value at t-4, t-1, t0, t+3, t+4, and t+5 conveyed bad news, therefore investors overreacted to alter stock prices, resulting in disparities in trading volume activity before to and following the announcement of cash distributions. Indirectly, the declaration of cash dividends can impact the trading volume activities of LQ45 Index-listed businesses.